1995
DOI: 10.1111/j.1399-302x.1995.tb00113.x
|View full text |Cite
|
Sign up to set email alerts
|

Clonal diversity of the Streptococcus mitis biovar 1 population in the human oral cavity and pharynx

Abstract: A total of 250 isolates of oral streptococci were recovered from swabs of oropharyngeal surfaces of 3 members of one family. All isolates were examined by biochemical and serological means, and 106 isolates were identified as Streptococcus mitis biovar 1. These were typed by restriction endonuclease analysis using the enzymes EcoRI and HaeIII and further characterized by their whole-cell polypeptide profile patterns in sodium dodecyl sulfate-polyacrylamide gel electrophoresis. In addition, rabbit antisera rais… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
63
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 30 publications
13
63
1
Order By: Relevance
“…The identity of the ribotype and age (months) of the infant at which the saliva was collected are indicated at the bottom of each column. and replacement of S. mitis (Hohwy and Kilian, 1995;Fitzsimmons et al, 1996;Hohwy et al, 2001;Kirchherr et al, 2005), we hypothesized that the concentration of S. mitis-specific SIgA antibody in saliva is limited because the mucosal immune system has a very short exposure to the individual clones of S. mitis that appear and rapidly disappear from the mouth. Under these conditions, it might be expected that the secretory immune system would respond to those antigens that are common to every clone of S. mitis because these provide a 'stationary target'.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The identity of the ribotype and age (months) of the infant at which the saliva was collected are indicated at the bottom of each column. and replacement of S. mitis (Hohwy and Kilian, 1995;Fitzsimmons et al, 1996;Hohwy et al, 2001;Kirchherr et al, 2005), we hypothesized that the concentration of S. mitis-specific SIgA antibody in saliva is limited because the mucosal immune system has a very short exposure to the individual clones of S. mitis that appear and rapidly disappear from the mouth. Under these conditions, it might be expected that the secretory immune system would respond to those antigens that are common to every clone of S. mitis because these provide a 'stationary target'.…”
Section: Discussionmentioning
confidence: 99%
“…In parallel with our studies on the salivary mucosal immune response to commensal oral bacteria, we and others have examined the population dynamics of S. mitis biovar 1 in the mouth and have shown that, while this bacterium is stable at the species level, it exhibits significant clonal turnover and replacement (Hohwy and Kilian, 1995;Fitzsimmons et al, 1996;Hohwy et al, 2001;Kirchherr et al, 2005). Indeed, most of the clones in the current study were isolated at a single sampling visit and could not be re-isolated at the successive visit, 2 months later.…”
Section: Introductionmentioning
confidence: 99%
“…Whole-cell DNA was purified as described by Hohwy & Kilian (1995). Approximately 10 mg DNA was digested with EcoRI and treated with RNase.…”
Section: Methodsmentioning
confidence: 99%
“…Other observations add to our skepticism. First, nonpathogenic bacteria show extensive diversity at their rfb loci (33,34), abrogating extensive, direct exposure to the immune system as a necessity for extreme variability; in addition, loci not encoding surface antigens show high diversity (e.g., the hsd locus; see refs. 5 and 35).…”
mentioning
confidence: 99%